2013
DOI: 10.5334/jbr-btr.179
|View full text |Cite
|
Sign up to set email alerts
|

Dual Energy CT: added value in gouty arthritis

Abstract: gouty arthritis is an inflammatory reaction as a result of monosodium urate crystal deposition in synovial fluid and periarticular soft tissue. it is the most common form of inflammatory arthritis with an estimated prevalence of 5 per 1000 in the usa. Clinical diagnosis is difficult and definite diagnosis with positive urate crystal aspiration often is made late in the disease process. dual energy computer tomography (dECt) is a relative new non-invasive imaging modality that is able to distinguish urate cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Recent studies showed that imaging techniques may have a potential role in the identification of MSU crystals, including plain radiography, ultrasonography, MRI, conventional computed tomography (CT), and dual-energy computed tomography (DECT). DECT has been reported to have greater sensitivity (78–89%) and specificity (93–100%) than the other techniques for gout diagnosis [ 8 11 ]. Thus, DECT is regarded as a critical appliance to diagnose gout patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that imaging techniques may have a potential role in the identification of MSU crystals, including plain radiography, ultrasonography, MRI, conventional computed tomography (CT), and dual-energy computed tomography (DECT). DECT has been reported to have greater sensitivity (78–89%) and specificity (93–100%) than the other techniques for gout diagnosis [ 8 11 ]. Thus, DECT is regarded as a critical appliance to diagnose gout patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DECT imaging has been used in the clinical diagnosis and treatment of gout as an emerging new method and has a high value for the assessment of gout [26][27][28], Some literature had described the ability of DECT in detecting MSU. Choi et al [13] noted that DECT can help identify subclinical tophi.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dual‐energy CT imaging is an emerging new method used in the clinical treatment of gout, and has a high value for the assessment of gout . In this study, we used dual‐energy CT to analyze the distribution and features of urate crystals around the foot in patients with gout, and simultaneously analyzed the association between features of these deposits and attacks of gouty arthritis.…”
Section: Discussionmentioning
confidence: 99%